Impact of Digital Marketing in Purchase Decision and Buying Behaviour of Gen Z - Nartea, Mecmack Avila; Barrera, Reynaldo T. (Universitas Semarang, 2023)
Introduction: Along with the technological development and radical growth of internet of things, digital marketing also risen as a vital tool in promoting products and services. Understanding the attitude and consumer buying behavior online also rapidly growing in the e-business limelight however, in the Philippine context there were few literatures about Gen Z online buying behavior. The purpose of the study is to determine the impact of digital marketing on the online purchase decision and buying behavior of Filipino Gen Z consumers. Methods: A survey research method was utilized to collect data from randomly selected 378 Gen Z online shoppers from Polytechnic University of the Philippines. A Pearson-r correlation was used to determine if there was a significant relationship between the variables. Findings: The results revealed that there were significant relationships between digital marketing and consumer purchase decisions. Consumer Purchase Decision was also affected by social, personal, and psychological factors. The result also revealed that time spent in social media sites does not influence the buying behavior of Gen Z in Pre-purchase, Purchase, and Post-purchase stages. Originality: The study becomes novel since there were very few studies about digital marketing in developing countries. Furthermore, there are no previous studies examining Filipino Gen Z’s Online Buying Behavior in Purchase Decision Process in Pre-Purchase, Purchase, and Post-purchase stages. This study makes an important contribution to behavioral research in developing countries.